Аналіз принципу роботи фотодетектора «лазерного мікрофону» - Ковальчук, Ю. О. (ХНУРЭ, 2008)
The given work is devoted to research of possibilities of laser systems of acoustic reconnais sance. Research consists in building and the analysis of corresponding quantitative models, for obtaining the results which can be used in process of assessment of the information leakage channel and building the measures of protection.
Keywords: фотодетектор; «лазерний мікрофон»